Collagen crosslinking: effect on structure, mechanics and fibrosis progression. (19th October 2021) - Kong, Wenyu; Lyu, Cheng; Liao, Hongen; Du, Yanan
Abstract: Biophysical properties of extracellular matrix (ECM), such as matrix stiffness, viscoelasticity and matrix fibrous structure, are emerging as important factors that regulate progression of fibrosis and other chronic diseases. The biophysical properties of the ECM can be rapidly and profoundly regulated by crosslinking reactions in enzymatic or non-enzymatic manners, which further alter the cellular responses and drive disease progression. In-depth understandings of crosslinking reactions will be helpful to reveal the underlying mechanisms of fibrosis progression and put forward new therapeutic targets, whereas related reviews are still devoid. Here, we focus on the main crosslinking mechanisms that commonly exist in a plethora of chronic diseases (e.g. fibrosis, cancer, osteoarthritis) and summarize current understandings including the biochemical reaction, the effect on ECM properties, the influence on cellular behaviors, and related studies in disease model establishment. Potential pharmaceutical interventions targeting the crosslinking process and relevant clinical studies are also introduced. Limitations of pharmaceutical development may be due to the lack of systemic investigations related to the influence on crosslinking mechanism from micro to macro level, which are discussed in the last section. We also propose the unclarified questions regarding crosslinking mechanisms and potential challenges in crosslinking-targeted therapeutics development.